Comparison of design education according to the views of Gropius and Buchanan - Raineri Bernain, Gonzalo (Base Diseño e Innovación, 2016)
In "The battle between old and modern books", Jonathan Swift in the XVIII century performs a characterization of a long intellectual debate even existing today in part of the academy. This division is given by the paleoteric knowledge or the old, classic, and, in contrast, the "neoteric" which reflected the new theoretical-scientific knowledge, which would drag human development forward. Design was located within paleoteric, considered at the time as something of basic characteristics and based on the empirical historic experience.